EFEKTIVITAS BIMBINGAN BELAJAR DALAM MENINGKATKAN SEMANGAT BELAJAR SISWA DI SDN LUOK MANIPI - Dini; Hamna; Moh Rudini (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Madako Tolitoli, 2025)
The purpose of this study is to analyze the extent to which tutoring can have a positive impact on increasing students' enthusiasm for learning. This research is motivated by the condition of some students who lack enthusiasm in learning due to difficulty understanding the material, weak internal motivation, and irregular study habits. The research method used is qualitative with a descriptive approach. The research subjects consisted of students who participated in the tutoring program. Data were collected through observation and interview techniques. The results of the study indicate that tutoring contributes significantly to fostering enthusiasm for learning, which is characterized by increased student engagement, learning motivation, discipline, self-confidence, and academic results. Therefore, tutoring can be considered an effective strategy for improving the quality of learning.